Multiscale analysis of woven composite structures in MSC.Nastran. (September 2019) - Liu, Xin; Gasco, Federico; Yu, Wenbin; Goodsell, Johnathan; Rouf, Khizar
Highlights: A novel multiscale modeling approach is integrated into MSC.Nastran. Conventional beam and shell elements are powered to analyze woven composite structures. Loss of accuracy using homogenized properties with beam and shell elements are studied. Direct numerical simulation reveals the accuracy and efficiency of the proposed approach. A graphical user interface is developed to serve as a constitutive modeling module in MSC.Nastran. Abstract: In the finite element analysis (FEA) of composite structures, shell and beam elements with homogenized material properties are often used to reduce the computational costs and modeling efforts. However, significant loss of accuracy may occur due to constitutive modeling limitations of commercially available software packages for complex mesostructures such as woven composites. In this paper, CQUAD4, CQUAD8 and CBEAM elements in MSC.Nastran have been enabled to analyze complex woven composite structures using mechanics of structure genome (MSG). The plate and beam stiffness matrices are computed using MSG plate and beam models and transformed into MSC.Nastran element and material properties to perform the structural analysis. A three-dimensional (3D) orthogonal woven plate is analyzed using MSC.Nastran CQUAD4 elements based on MSG plate model. In addition, a 3D woven beam with extension-bending couplings is analyzed using MSC.Nastran CBEAM elements with homogenized properties with the help of MSG beam model. The beam and shell elements in MSC.Nastran powered by MSG models provide a new way to analyze complex woven composite structures. A graphical user interface (GUI) has been developed for MSC.Nastran to incorporate the constitutive modeling and to enable the automation of the information passing between constitutive modeling and structural analysis.